Something more - Dailey, Janet (New York : Zebra Books, 2008)
When he stumbles upon the key to solving an old mystery involving a stolen fortune in gold, rancher Luke McCallister decides to help the great-granddaughter of one of the bandits find the treasure, which leads them both on a powerful journey of danger, faith, trust, and love.
Keywords: Treasure troves -- Fiction; Ranch life -- Fiction; Wyoming -- Fiction; Love stories